IMPOLITENESS STRATEGIES PERFORMED BY THE MAIN CHARACTER IN “THE PROPOSAL” MOVIE - Muchamad Daffa; Zia Hisni Mubarak (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This research aimed to investigate impoliteness strategies that used in The Proposal movie by the main character. This strategies based on Culpeper's theory (1996). This study used descriptive qualitative method to analyze the data and to describe the result of this analysis. The source of the data is The Proposal movie and script of the movie. The researcher does the research by watch the movie, check the reliability between the movie and the script, identify character’s utterance, and identify impoliteness strategies by the main character utterance. The researcher discover five strategies of impoliteness based on Culpeper's theory (1996) that used by the main character in The Proposal movie, there are positive impoliteness, negative impoliteness, sarcasm or mock impoliteness, bald on record, and withholding impoliteness. The result from this study that researcher found five impoliteness strategies through the main character in The Proposal (2009) movie, there are 4 bald on record, 4 positive impoliteness, 5 negative impoliteness, 1 sarcasm or mock impoliteness, and 1 withholding impoliteness.